MENINGKATKAN POTENSI USAHA UMKM GAMBART MELALUI MEDIA SOSIAL - Anggraini, Feny Savira; Atikah, Fifi; Taqiyyah, Mia Risyah; Sulaeman, Sania Khaira Ikhsanti; Nurlela, Siti (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2023)
This research aims to explore the potential of TikTok social media utilization in improving the business of MSMEs "GambArt". One of the problems faced is the lack of knowledge of partner employees and owners regarding the application of information technology as a support system in the production process. Therefore, this research aims to see the increased business potential of MSMEs "GambArt" in supporting marketing effectiveness and efficiency. In this research, a qualitative descriptive method is used to get an overview of the application concept using a design thinking approach. This design thinking approach includes the stages of Empathize, Define, Ideate, Prototype, and Test. The results show that TikTok social media is an effective medium in showcasing the art products of MSMEs "GambArt" through interesting and creative short video content. This allows "GambArt" MSMEs to attract the attention of a wider audience, increase brand awareness, and expand the network of potential customers.The implications of this research can help similar MSMEs in utilizing TikTok social media as an effective tool to expand their reach and increase business growth. In order to support this, we created social media accounts such as TikTok and Instagram to help "GambArt" MSMEs to reach their full potential. With a presence on these platforms, it is expected that "GambArt" MSMEs can connect with more potential customers, expand their market share, and optimize their overall business performance.